Perceptions, Knowledge, and Attitudes of Students towards Safety Practice in Culinary Laboratories - Mohd Erfy Ismail; H. Harun; A.R. Abdul Razzaq; I. Irwan Mahazir; N. Abd Samad; H. Othman (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
The variety of tools and equipment requires a modern and sophisticated safety management for practical works in a laboratory. It is susceptible to the risk of an accident if safety is ignored. Therefore, this study conducted a descriptive survey to assess perceptions, knowledge, and attitudes of students in the course of culinary about safety practices in culinary laboratories. The population consisted of 90 students from the first year until the fourth year, which comprises the entire study population involved in practical works in the laboratory. Nonrandom sampling using a purposive sampling technique used as the sampling method and involved 60 samples. The instruments were a questionnaire to obtain information. Data were collected and analyzed statistically. Based on the pilot study analysis, the reliability of the instrument was 0.91 categorized as high. Results showed that good safety practices give positive influence on knowledge, attitudes, and perceptions of students towards safety practice in culinary laboratories. The study showed that a safe and orderly work culture is capable of creating disciplined and responsible attitudes.